2021
DOI: 10.3390/v13091796
|View full text |Cite
|
Sign up to set email alerts
|

Histotype-Dependent Oligodendroglial PrP Pathology in Sporadic CJD: A Frequent Feature of the M2C “Strain”

Abstract: In sporadic Creutzfeldt-Jakob disease, molecular subtypes are neuropathologically well identified by the lesioning profile and the immunohistochemical PrPd deposition pattern in the grey matter (histotypes). While astrocytic PrP pathology has been reported in variant CJD and some less frequent histotypes (e.g., MV2K), oligodendroglial pathology has been rarely addressed. We assessed a series of sCJD cases with the aim to identify particular histotypes that could be more prone to harbor oligodendroglial PrPd. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a recent study showed that NG2 glia, oligodendrocyte-lineage cells, exert a protective effect against prioninduced neurotoxicity by interacting with microglia and inhibiting critical signalling pathways 79 . It is also noteworthy that in human patients, oligodendroglial PrP pathology has been reported in certain histotypes of sCJD 80 . Therefore, oligodendrocytes may be implicated in prion pathogenesis, which is further supported by the convergence of the two non-PRNP sCJD risk factors, STX6 and GAL3ST1, in this cell type.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a recent study showed that NG2 glia, oligodendrocyte-lineage cells, exert a protective effect against prioninduced neurotoxicity by interacting with microglia and inhibiting critical signalling pathways 79 . It is also noteworthy that in human patients, oligodendroglial PrP pathology has been reported in certain histotypes of sCJD 80 . Therefore, oligodendrocytes may be implicated in prion pathogenesis, which is further supported by the convergence of the two non-PRNP sCJD risk factors, STX6 and GAL3ST1, in this cell type.…”
Section: Discussionmentioning
confidence: 95%
“…The differing morphologies of plaque‐like deposits depending on the regions might also be a characteristic of MV2K + C. Furthermore, we found synaptic immunoreactive structures along the axons in the cerebral cortex, and this finding probably includes perineuronal apical axon staining. The coarse deposits along the axon have been frequently seen in VV2 but are not often described in MV2K + C 19 . The neuropathological feature of MV2K is similar to VV2 2 .…”
Section: Discussionmentioning
confidence: 99%